Seroprevalence of Bordetella pertussis immunoglobulin G antibodies among children in Samsun, Turkey - Özkal, Atay; Şensoy, Gülnar; Acuner, Çağatay; Belet, Nurşen; Güney, Akif Koray (The Turkish Journal of Pediatrics, 2012)
In this study, we aimed to investigate anti-pertussis immunoglobulin (Ig) G antibodies in the serum of children in our region vaccinated against pertussis with four doses. Between August 2008-2009, antibody levels to Bordetella pertussis (B. pertussis) antigens were studied in 385 serum samples from healthy children aged 1.5-18 years (y) vaccinated against pertussis in Samsun, Turkey. The study population was divided into six groups according to ages: 1.5-3 y; 4-5 y; 6-8 y; 10-12 y; 13-15 y; and 16-18 y. IgG antibodies to B. pertussis antigens were measured with a commercial ELISA kit. Mean age of the children was 9.6 +/- 5.3 y. Anti-pertussis IgG titers were positive in 48.3% of the cases. The lowest positivity rate was determined in the 4-5 y age group (28.1%) and the highest rate in the 16-18 y age group (64.2%). Geometric mean titer of anti-pertussis antibodies was 39.2 IU/ml, and again the lowest value was obtained in the 4-5 y age group (23.3 IU/ml) and the highest in the 16-18 y age group (51.4 IU/ml). The antibody levels to B. pertussis antigens significantly decrease 4-6 years after vaccination and again increase in school children, possibly due to natural infection.